Streets of Terror: Marginalization, Criminalization, and Authoritarian Renewal - Scraton, Phil (Social justice, 2004)
Part of a special issue on resisting militarism and globalized punishment. The development of the authoritarian state in the U.S. and the U.K. is discussed. It is argued that this authoritarianism has resulted in increased criminalization. It is noted that this authoritarian approach to crime tends to target the marginalized, but fails to address the everyday struggles of members of this group.